Impurities of crude glycerol and their effect on metabolite production - Samul, Dorota (Springer Berlin Heidelberg, 2013)
Glycerol is a valuable raw material for the production of industrially useful metabolites. Among many promising applications for the use of glycerol is its bioconversion to high value-added compounds, such as 1,3-propanediol (1,3-PD), succinate, ethanol, propionate, and hydrogen, through microbial fermentation. Another method of waste material utilization is the application of crude glycerol in blends with other wastes (e.g., tomato waste hydrolysate). However, crude glycerol, a by-product of biodiesel production, has many impurities which can limit the yield of metabolites. In this mini-review we summarize the effects of crude glycerol impurities on various microbial fermentations and give an overview of the metabolites that can be synthesized by a number of prokaryotic and eukaryotic microorganisms when cultivated on glycerol.